2007
DOI: 10.1007/s00335-007-9009-5
|View full text |Cite
|
Sign up to set email alerts
|

A growth QTL (Pbwg1) region of mouse chromosome 2 contains closely linked loci affecting growth and body composition

Abstract: Previous QTL studies have identified 24 QTLs for body weight and growth from 3 to 10 weeks after birth in an intersubspecific backcross mouse population between C57BL/6J and wild Mus musculus castaneus that has 60% of the body size of C57BL/6J. The castaneus allele at the most potent QTL (Pbwg1) on proximal chromosome 2 retards growth. In this study we have developed a congenic strain with a 44.1-Mb interval containing the castaneus allele at Pbwg1 by recurrent backcrossing to C57BL/6J. The congenic mouse deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
42
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 32 publications
6
42
0
Order By: Relevance
“…The 95% confidence interval (CI) for each QTL was determined with a 1.5-LOD drop from the QTL peak (32). The mode of inheritance of alleles at the QTL detected was determined by two statistical tests using Map Manager QTX20b (13). First, one of additive, dominance, and recessive regression models was contrasted with a no-QTL model.…”
Section: Methodsmentioning
confidence: 99%
“…The 95% confidence interval (CI) for each QTL was determined with a 1.5-LOD drop from the QTL peak (32). The mode of inheritance of alleles at the QTL detected was determined by two statistical tests using Map Manager QTX20b (13). First, one of additive, dominance, and recessive regression models was contrasted with a no-QTL model.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous congenic analysis using B6.Cg-Pbwg1 [6] and another QTL study using the CAST/Ei inbred strain originating from wild M. m. castaneus trapped in Thailand [11] reported that the Cas allele increases body weight and weight gain at early ages. Thus, this may be the first study using castaneus mice that has revealed a QTL with an increasing effect on growth at later ages.…”
mentioning
confidence: 98%
“…Mice were sacrificed under ether anesthesia at 10 weeks of age. As described previously [6], total body length and tail length were measured and head-body length and body mass index (g/cm 2 ) were calculated. Six internal organs (heart, lung, spleen, liver, and both kidneys and testes) were weighed.…”
mentioning
confidence: 99%
See 2 more Smart Citations